An evaluation of game-based computer science course designs: The example of minecraftedu - Tonbuloglu, Betul (SPRINGER, 2024)
The purpose of this research is to evaluate the potential of use for computer science course designs (CSCD) created by game-based learning method. Qualitative case study was used as the research design. CSCDs created for Minecraft Education Edition (MinecraftEdu) were examined in the context of various criteria by document analysis method, and semi-structured interviews were conducted with teachers actively using MinecraftEdu in their classes. The research revealed that the CSCDs created for MinecraftEdu primarily aimed at developing coding and design skills, underscored interdisciplinary collaboration, laid more emphasis on cognitive-psychomotor achievements with curriculum eligibility. It was acknowledged that introduction, body and conclusion parts have an elaborate design in majority of course designs according to Gagne's Events of Instruction Model, and yet, more attention should be paid to gaining the learner's attention, stimulating recall of prior learning, giving feedback, and ensuring retention and transfer. Despite increasing interest and trend towards educational games and game-based learning environments, there are limited number of studies that can help teachers evaluate the games that can be most effective in their fields and different learning contexts. Therefore, it is anticipated that this study will contribute to the related literature on game-based course designs and applicability.
Keywords: Game-based learning; Minecraft Education Edition; Educational technology; Lesson planning; Program evaluation; EDUCATION; Education & Educational Research